Secondary Fractures Following Internal Fixation in Two Horses - Gaughan, E. M.; Duchar, N. G. (Veterinary and Comparative Orthopaedics and Traumatology, 1989)
Implant associated fractures have not been reported in horses. Two horses were evaluated for fractures in the fore limbs, occurring subsequent to previous fracture repair. Previously, the horses had sustained fractures of unusual configurations which were repaired using internal fixation. Following repair and healing of the fractures, secondary fractures occurred in the same bone, but in a different (more common) configuration. The first horse was evaluated ten months following lag screw fixation of a longitudinal fracture of the proximal phalanx in a frontal plane. This horse presented with a more typical comminuted fracture in the sagittal plane with the screws from the first fixation lying in the fracture line. This fracture was successfully treated with a cast. The second horse was examined eightteen months after repair of a medial sagittal slab fracture of the third carpal bone. The horse presented with a more typical dorsal slab fracture of the third carpal bone with the previously placed lag screw lying in the fracture line. The screw was removed and a lag screw was placed perpendicular to the new fracture plane through the dorsal surface of the third carpal bone to repair the fracture.
Keywords: Secondary fracture; Internal fixation; Horse